2020
DOI: 10.1007/s11239-020-02184-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes after percutaneous coronary intervention for early versus late and very late stent thrombosis: a systematic review and meta-analysis

Abstract: Whether the clinical outcomes of stent thrombosis (ST) are different when stratified by time of occurrence remains unclear. The objective of this study was to compare the short-and long-term clinical outcomes after percutaneous coronary intervention (PCI) for early stent thrombosis (EST) versus late stent thrombosis (LST) and very late stent thrombosis (VLST). We enrolled eligible studies searched from the main electronic databases (EMBASE, PubMed, Cochrane). The primary endpoints were in-hospital, 30-day, 1-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“… 23 However, in-hospital mortality in our study was observed to be much higher than the conventionally reported mortality rate after primary PCI. One of the possible reasons was the higher distribution of acute or sub-acute ST as a recent systematic review and meta-analysis reported significantly worst short- and long-term clinical outcomes among patients with early ST compare to late or very late ST. 24 Supporting these findings He C et al 25 also reported no significant differences in outcomes after late stent thrombosis compared to de novo lesion. However, contrary to the observations of these studies, Ergelen M et al 26 reported significantly higher in-hospital cardiovascular mortality among ST induced STEMI patients (10.2% vs. 5.3%; p = 0.02) as compared to de novo lesion, hence, less effectiveness of primary PCI for STEMI due to ST was concluded by this study.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“… 23 However, in-hospital mortality in our study was observed to be much higher than the conventionally reported mortality rate after primary PCI. One of the possible reasons was the higher distribution of acute or sub-acute ST as a recent systematic review and meta-analysis reported significantly worst short- and long-term clinical outcomes among patients with early ST compare to late or very late ST. 24 Supporting these findings He C et al 25 also reported no significant differences in outcomes after late stent thrombosis compared to de novo lesion. However, contrary to the observations of these studies, Ergelen M et al 26 reported significantly higher in-hospital cardiovascular mortality among ST induced STEMI patients (10.2% vs. 5.3%; p = 0.02) as compared to de novo lesion, hence, less effectiveness of primary PCI for STEMI due to ST was concluded by this study.…”
Section: Discussionmentioning
confidence: 82%
“…Still, stent thrombosis (ST) remained a relatively rare but dreaded complication of PCI. 2 The introduction of drug-eluting stents (DES) was undoubtedly a milestone however, ST was one of the main safety concerns with 1st generation DES this has been addressed in the 2nd generation DES with biodegradable or biocompatible durable polymer and stent platform with thinner strut. 3 , 4…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis by Yang et al, patients with early ST were associated with an increased risk of in-hospital and 30-day mortality (risk ratio (RR) 1.67 95% CI 1.17, 2.37 and 2.05 95% CI 1.58, 2.67, respectively). 28 The increased risk of complications among this specific ST onset group, despite adjustment for their higher risk profile at baseline, could be possibly attributed to differences in the aetiology and vascular bed status at different times of ST onset. Early ST is more commonly caused by stent underexpansion and acute malapposition as well as early discontinuation of antiplatelet therapy especially at a time when re-endothelialisation has not occurred, while late and very late ST have been previously attributed to late stent malapposition, delayed endothelialisation and neoatherosclerosis.…”
Section: Discussionmentioning
confidence: 86%
“…The most recent meta-analysis conducted Yang et al [33] investigated the link between the timing of stenting the clinical outcomes. Results revealed that patients with early stenting had worse clinical outcomes than patients with late or very late stenting in both short-and long-term outcome after PCI.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in late and very late stenting, the thrombus formation was more like an advanced evolution, permitting enough time for development of collateral circulation. However, in early stenting, the capability to establish coronary collateral circulation may be reduced by the rapid onset of stent thrombosis due to the higher on-treatment platelet reactivity, which may lead to a larger infract size of the myocardium and higher rates of adverse events [33] .…”
Section: Discussionmentioning
confidence: 99%